Blood glucose and sepsis score on sepsis patients requiring insulin therapy - Mohamad Suhaimi F.; Jamaludin U.K.; Abdul Razak N.N.; Pretty C.G.; Md. Ralib A.; Mat Nor M.B.; Dzaharudin F. (Springer Verlag, 2023)
Biomedical engineering; Blood; Diagnosis; Glucose; Insulin; Blood glucose; Blood glucose level; Clinical guideline; Insulin sensitivity; Insulin therapy; Patient condition; Provide guidances; Sepsis; Patient treatment